Gear Mapping Technology Based on Differential Envelope Principle. (1st April 2021) - Liu, Yangpeng; Guo, Jingyang; Ding, Jianjun; Duan, Duanzhi; Jiang, Yuerong; Li, Changsheng; Zhao, Wei; Jiang, Zhuangde
Abstract : It is proposed that the complex molding process and the scanning process should be unified through the differential envelope principle. After scanning the surface of the part with the contact sensor, the contour coordinates of the measured surface are calculated by the trajectory of the center of the ball, and the contour data of the complex linear surface is extracted. Then, the intelligent analysis and calculation of precision generating surface parameters and quantitative adjustment are carried out, and the exact reverse method of the special line parts with characteristic parameters is studied. There is only micron scale difference between the reverse result and the nominal value. This technology is applied to the closed-loop manufacturing process of gear parts, which reduces the dependence on the artificial experience when the machining parameters of the cylindrical gear processing equipment is adjusted and provides an effective solution for the digital and intelligent manufacturing of the parts.